Isolated left ventricular non compaction as possible cause of athletic training suspension: a preliminary study on screened athletes - Martinoli, R.; Papetti, F.; Dofcaci, A.; Mercurio, V.; Pirruccio, G.; Pirelli, M.; Piccirilli, S.; Greci, G.; Lanzillo, C.; Sansoni, I.; Saccucci, P.; Banci, M. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of this paper was to determine the prevalence of isolated left ventricular noncomapction (ILVNC) in a sample of 150 athletes send by sports doctors to the Valmontone Hospital`s Cardiology Division in a span of about three years, with particular interest in non-compacted segments evaluation. The prevention of cardiovascular complications occurring during sporting activity requires detection of pathologies most often clinically latent but whose first presentation can be sudden cardiac death. In Italy, the pre-participation screening program comprises family history and personal cardiac history, clinical examination and electrocardiography. Subjects with abnormalities are further investigated by stress test, echocardiography and laboratory investigations, and those with significant abnormalities are disqualified from sports training and competition. ILVNC results in multiple trabeculations in the left ventricular myocardium and it is postulated to be caused by intrauterine arrest of compaction of the myocardial fibres and meshwork, an important process in myocardial development. This cardiomyopathy should be considered one of the structural cardiac abnormalities responsible for sudden cardiac death. Methods: There were 150 athletes seen in the Cardiology Division from 2007 to 2010 for an echocardiographic evaluation in order to clarify the nature of physical examination and/or electrocardiogram abnormalities. Echocardiographic diagnosis of ILVNC was based on criteria published by Jenni et al., and by Stölberger et al. Results: Twenty-four of the 150 tested resulted positive for ILVNC (16.0%). This high prevalence is justified because it was a population originally selected because of electrocardiographic abnormalities. Conclusion: We believe that in case of unspecific ECG findings, it would be useful to perform echocardiographic examination in order to highlight structural defects. We also believe that it is very important to contemplate ILVNC between the causes of sudden death in young competitive athletes.